Market Power in Agricultural Land Markets: Concepts and Empirical Challenges - Alfons Balmann; Marten Graubner; Daniel Mul̈ler; Silke Huẗtel; Stefan Seifert; Martin Odening; Jana Plogmann; Matthias Ritter (German Journal of Agricultural Economics (GJAE), 2021)
This paper provides review about challenges and opportunities to assess and quantify market power in agricultural land markets. Measuring land market power is challenging because the characteristics of this production factor hinder the direct application of familiar concepts from commodity markets. Immobility, fixed availability, and large heterogeneity of land and potential users contradict assumptions of fictitious point market for homogeneous goods. Moreover, the use of concentration indicators for policy assessments is hampered by two problems. First, defining the relevant regional size of the market is challenging and concentration indicators are not robust with regard to market size and number of actors. Second, high concentration of land ownership or land operation may point at potential market power, but it may also be the result of an efficient allocation of land due to structural change in agriculture. The aforementioned challenges are illustrated with a case study for the Federal State of Brandenburg in Germany. Using available data for land sales, a regression analysis reveals a negative relationship between land use concentration and farmland prices. This result can be interpreted as an indication of market power on the buyer side in agricultural land markets. However, it is hardly possible to translate this finding into recommendations for land market regulations because the evaluation of the potential misuse of dominant positions in land markets requires a case-specific analysis. Providing evidence for the exertion of market power in land markets is extremely complex and deserves further attention from researchers and politicians.
Keywords: 330; market power; bargaining power; concentration; land markets